2020
DOI: 10.31254/jsir.2020.9202
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of bioactive compounds in hydroalcohol extract of Phyllanthus amarus Schum. and Thonn. leaf using GC-MS analysis

Abstract: Phyllanthus amarus is one of the most important medicinal plant in tropical and subtropical nations which are used for stomach, liver, kidney and spleen diseases treatment. This work involves the elucidation of the phytochemical constituents in 70% ethanolic leaf extract of P. amarus. Phytochemical screening, quantitative and gas chromatography-mass spectrometry (GC-MS) analyses were carried out on the extract. The qualitative and quantitative analyses showed the presence of the following phytochemicals and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Indole derivatives have different biological activities, i.e., anti-inflammatory, antiviral, antioxidant, anticancer and antimicrobial [28] . These results revealed that the chemical constituents of the methanol extract of P. emblica leaves are in agreement with previous studies reported by [29,30]…”
Section: Gc-ms Analysissupporting
confidence: 93%
“…Indole derivatives have different biological activities, i.e., anti-inflammatory, antiviral, antioxidant, anticancer and antimicrobial [28] . These results revealed that the chemical constituents of the methanol extract of P. emblica leaves are in agreement with previous studies reported by [29,30]…”
Section: Gc-ms Analysissupporting
confidence: 93%
“…Analysis. Te analysis was conducted at the Scientifc and Technological Research Equipment Centre of Chulalongkorn University in Bangkok, Tailand [22]. GC-MS analysis involved an Agilent Technologies 19091S-433 gas chromatograph (GC) coupled with an Agilent 5973 mass selective detector (MSD), controlled by Agilent Chemstation software.…”
Section: Gas Chromatography-mass Spectrometric (Gc-ms)mentioning
confidence: 99%
“…It is an important plant of the Indian Ayurvedic system of medicine, which is used in treating problems of the stomach, genitourinary system, liver, kidney, and spleen. Ajayi et al [48] analyzed multiple bioactive compounds in mg/100 g of leaf extract as phenol ( (3,4-dimethoxyphenyl)ethyl]-2-nitro-(12.68%), hexadecanoic acid, ethyl ester (12.63%), beta tocopherol (12.63%), and phytol (12.61%). The phytochemical concentrations in its leaves are 0.73 ± 0.01%, 1.85 ± 0.03%, 1.12 ± 0.01%, 1.80 ± 0.01%, 1.59 ± 0.50%, 0.13 ± 0.10%, and 0.86 ± 0.01%, for saponins, tannins, phenolics, anthocyanins, alkaloids, triterpenoids, and glycosides, respectively, while in the roots, they are are 0.91 ± 0.01%, 1.53 ± 0.03%, 0.70 ± 0.01%, 2.97 ± 0.10%, 2.47 ± 0.03%, 0.62 ± 0.01%, 0.90 ± 0.01%, and 2.02 ± 0.10% for saponins, tannins, phenolics, steroids, flavonoids, anthocyanins, glycosides, and coumarins, respectively [26].…”
Section: Phyllanthus Amarusmentioning
confidence: 99%